2018
DOI: 10.1002/jpen.1176
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Balance During Venovenous Extracorporeal Membrane Oxygenation Support: Preliminary Results of a Prospective, Observational Study

Abstract: These preliminary findings suggest that current guidelines for estimating protein needs in critically ill patients may be adequate for nonobese patients receiving VV ECMO. However, current protein recommendations for critically ill obese patients may not be adequate during VV ECMO support, possibly related to significantly higher rates of catabolism. Future studies with a larger cohort of patients are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
(49 reference statements)
1
10
0
3
Order By: Relevance
“…Preliminary findings of NB results suggested that utilizing guidelines for general critical illness for patients on VV ECMO may be sufficient to meet the needs of nonobese patients but appeared suboptimal in obese patients. 8 However, in our current larger sample set, it appears that both nonobese and obese patients on VV ECMO may require more than the SCCM/ASPEN recommendations of 1.2-2 g protein/kg ABW in patients with BMI < 30 kg/m 2 , >2 g protein/kg IBW in patients with BMI 30-39.9 kg/m 2 , and ࣙ2.5 g protein/kg IBW in patients with BMI ࣙ 40 kg/m 2 . Cohort 1 contained a higher concentration of NB results completed in obese patients, whereas 80% of the NB results in cohort 2 were completed in nonobese patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary findings of NB results suggested that utilizing guidelines for general critical illness for patients on VV ECMO may be sufficient to meet the needs of nonobese patients but appeared suboptimal in obese patients. 8 However, in our current larger sample set, it appears that both nonobese and obese patients on VV ECMO may require more than the SCCM/ASPEN recommendations of 1.2-2 g protein/kg ABW in patients with BMI < 30 kg/m 2 , >2 g protein/kg IBW in patients with BMI 30-39.9 kg/m 2 , and ࣙ2.5 g protein/kg IBW in patients with BMI ࣙ 40 kg/m 2 . Cohort 1 contained a higher concentration of NB results completed in obese patients, whereas 80% of the NB results in cohort 2 were completed in nonobese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary work on NB demonstrated the catabolic nature of patients during VV ECMO support, with an average urinary urea nitrogen (UUN) excretion twice the normal range. Additionally, obese patients, defined as a body mass index (BMI) ≥ 30 kg/m 2 , exhibited significantly higher catabolism as measured by UUN excretion . Adequate nutrition support is pivotal to preventing or minimizing malnutrition of acute illness during such profound catabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 study aiming to investigate optimum protein intakes in patients receiving ECMO exists. This small study investigated the nitrogen balance in obese and nonobese adult patients receiving VV ECMO . Protein targets were set at 1.5–2.0 g/kg/d for nonobese patients and 2.0–2.5 g/kg/d for obese patients, with around 85% of this target being delivered.…”
Section: Dose Of Nutrition Supportmentioning
confidence: 99%
“…Ainda com relação às proteínas, um estudo realizado com o objetivo de investigar o catabolismo proteico durante o suporte da ECMO VV sugeriu que o estado nutricional dos pacientes pode influenciar no balanço nitrogenado. O resultado do balanço nitrogenado demonstrou que pacientes não obesos tiveram menor catabolismo do que pacientes com obesidade, respectivamente -1,7 ± 5,7 vs. -11,5 ± 9,6 29 . Entretanto, tratou-se de estudo observacional com amostra pequena, portanto, são necessários mais estudos para validar este dado.…”
Section: Necessidades Nutricionaisunclassified